Conception, Pregnancy, and Lactation Despite Chronic Intestinal Failure Requiring Home Parenteral Nutrition. (December 2015) - Buchholz, Bettina M.; Rüland, Anna; Kiefer, Nicholas; Poetzsch, Bernd; von Websky, Martin; Kalff, Jörg C.; Merz, Waltraut M.
Background: Short-term parenteral nutrition is commonly accepted to be safe in pregnancy, but knowledge about the management of pregnancy during long-term home parenteral nutrition (HPN) is sparse. Methods and Results: A systematic literature review revealed that the published experience is limited to 15 pregnancies with parenteral nutrition from preconception to delivery and beyond. Maternal morbidity was surprisingly low, and fetal outcome was good; however, micronutrient deficiencies may have contributed to fetal anomalies. Herein, we additionally report the case of a 26-year-old Caucasian woman with long-term HPN dependence secondary to short bowel syndrome caused by recurrent thromboembolic mesenteric infarctions who delivered a healthy fetus at 37 weeks of gestation. Individual macronutrient support and adequate micronutrient supplementation ensured normal maternal weight gain and fetal development. Based on the individual maternal risk of recurrent thrombosis, anticoagulant treatment was carefully titrated throughout pregnancy. Furthermore, loss of abdominal domain with a rigid maternal abdominal wall secondary to short bowel syndrome and multiple laparotomies resulted in food intolerance during the third trimester. Still, with multidisciplinary efforts, both mother and the breast-fed infant were in good health at 12 months after delivery. Conclusions: Taking the reported literature into consideration, we conclude that under the premise of optimal medical care, the risk:benefit ratio for pregnancy of HPN-dependent women seems to be justifiable. To minimize the risks, we recommend preconception counseling and early referral to a tertiary center offering both a high-risk pregnancy unit and a nutrition service. In particular, maternal micronutrient levels should be monitored.